Comparative studies of essential oils from Matricaria recutita L. - Panasenko, O. I.; Odyntsova, V. M.; Denysenko, O. M.; Mozul, V. I.; Holovkin, V. V.; Панасенко, Олександр Іванович; Одинцова, Віра Миколаївна; Денисенко, Ольга Миколаївна; Мозуль, Валентина Іванівна; Головкін, Володимир В'ячеславович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the work is to determine the component composition of the essential oil of medicinal chamomile, grown on the educational and research site of medicinal plants of Zaporizhzhia State Medical and Pharmaceutical University (ZSMPHU), and commercial essential oil that was purchased via the Internet. Materials and methods. The object of the study was chamomile essential oil obtained by hydrodistillation and commercial oil. Qualitative and quantitative determination of the components of essential oils was established using the chromato-mass spectrometric method on a high-performance gas chromatograph “Agilent 7890B GC System” (Agilent, SantaClara, CA, USA) with a mass spectrometric detector “Agilent 5977 BGC/MSD” (Agilent, SantaClara, CA, USA). Results. Dominant compounds of essential oil of chamomile, grown on the educational and research site of medicinal plants ZSMPHU were 2H-pyran-3-ol, tetrahydro-2,2,6-trimethyl-6-(4-methyl-3-cyclohexen-1-yl) ) – 7.54 %, chamazulene – 5.32 %, alpha-bisabolol – 4.30 %, 1H-cycloprop[e]azulen-7-ol, decahydro-3,1,7-trimethyl-4-methylene – 3.25 %, myrtenyl acetate – 3.03 %, azulene, 1,2,3,3a,4,5,6,7- octahydro-1,4-dimethyl-7-(1-methylethenyl) – 2.16 %, bisabolol oxide B – 1.86 %. Commercial chamomile essential oil was dominated by 3-methoxy-3-methylbutanol (56.15 %), diethyl phthalate (17.46 %), linalyl acetate (6.99 %), linalool (4.41 %). Conclusions. Industrial cultivation of chamomile in southern Ukraine shows a high biologically active substances content and can be in demand in the pharmaceutical industry’s consumer market for raw materials. Мета роботи – встановлення компонентного складу ефірної олії ромашки лікарської, вирощеної на навчально-дослідній ділянці Запорізького державного медико-фармацевтичного університету (ЗДМФУ), та комерційної ефірної олії, яка придбана через мережу Інтернет. Матеріали і методи. Об’єкт дослідження – ефірна олія ромашки, отримана методом гідродистиляції, та комерційна олія. Якісне та кількісне визначення компонентів ефірних олій здійснили з використанням хромато-мас-спектрометричного методу на високоефективному газовому хроматографі «Agilent 7890B GC System» (Agilent, SantaClara, CA, USA) з мас-спектрометричним детектором «Agilent 5977 BGC/MSD» (Agilent, SantaClara, CA, USA). Результати. Сполуки, що домінували в ефірній олії ромашки, яка вирощена на навчально-дослідній ділянці лікарських рослин лікарських рослин ЗДМФУ: 2H-pyran-3-ol, tetrahydro-2,2,6-trimethyl-6-(4-methyl-3-cyclohexen-1-yl) – 7,54 %, chamazulene – 5,32 %, alpha-bisabolol – 4,30 %, 1H-cycloprop[e]azulen-7-ol, decahydro-3,1,7-trimethyl-4-methylene – 3,25 %, myrtenyl acetate – 3,03 %, azulene, 1,2,3,3a,4,5,6,7-octahydro-1,4-dimethyl-7-(1-methylethenyl) – 2,16 %, bisabolol oxide B – 1,86 %. В комерційній ефірній олії ромашки лікарської переважали 3-methoxy-3-methylbutanol (56,15 %), diethyl phthalate (17,46 %), linalyl acetate (6,99 %), linalool (4,41 %). Висновки. Промислове культивування ромашки лікарської в умовах півдня України сприяє високому вмісту біологічно активних речовин і може бути затребуваним для споживчого ринку сировини, що використовують у фармацевтичній промисловості.
Порівняльні дослідження ефірних олій Matricaria recutita L.
Panasenko O. I. - ORCID ID: 0000-0002-6102-3455; Odyntsova V. M. - ORCID ID: 0000-0002-7883-8917; Denysenko O. M. - ORCID ID: 0000-0002-0448-4677; Mozul V. I. - ORCID ID: 0000-0002-4099-8042; Holovkin V. V. - ORCID ID: 0000-0001-7787-0969.
Keywords: Matricaria recutita L.; essential oil; chromatography-mass spectrometry; ефірна олія; хромато-мас-спектрометрія